SEED BUNDLE TRAINING REPORT: Climate-Smart Agriculture and Agribusiness Training - Chikoye, David; Consent, Sibeso (2024)
As part of efforts to enhance climate change resilience among youth and smallholder farmers in Zambia, Seed Bundle conducted a training program for 55 farmers in climate-smart agriculture and agribusiness from August 13th to 16th, 2024, at IITA's offices in Ngwerere. The program covered crucial areas such as managing climate resilience, farming as a business, and soybean seed production techniques.